Impacts of Forest Disturbance on Food Trees of Colobus angolensis in Kibonge Forest, Kenya - Chirchir, E.; Sudoi, V.; Kimanzi, J. (Africa Environmental Review Journal, 2022)
Forest disturbances by anthropogenic activities affects the size of a forest by reducing its size or changing the structure. This presents challenges to animals who depend on it for food and to environmental conservationists for it causes changes in hydrological cycles. Change of diet may be an important strategy to adjust to forest degradation. This study examines how changes in habitat, impact on food trees preferred by the folivorous C. angolensis, in Kibonge forest in Elgeyo- Marakwet County, Kenya. Data were collected between, July 2016 and July 2017. Observations were made to identify the level of forest disturbance on forest size and tree species fed on by two groups of C. angolensis in two regions of Kibonge forest (Mwen and Segen). Amount of canopy cover and nature of disturbance were established through ground field work on 87 sampled vegetation plots each measuring, 20m x 10m. Food trees were identified in the field and unidentified samples at the university of Eldoret arboretum. Selection ratio (S.R) were calculated for each eaten plant species in order to determine food preferred by C. angolensis. Data obtained were analyzed using Maximum Likelihood Classifier (MLC), SPSS, and xLSTAT. Chi square tests were carried out to establish variations between regions and species. Pearson correlation showed a significant reduction of Kibonge forest size (n=7, r=0.0956, p< 0.001). More tree species were concentrated on altitude 2400m (χ2=610.95, df =78, p<0.001). In dry season treespecies preferred by C. angolensis were Dombeya goetenzii, Nuxia congesta, and Cuppressus lustanica. In wet season were Prunus africana, Croton macrostachyus, Ficus thoninngii and Polyscius kikuyunensis. Defforestation of food trees is the major threat to C. angolensis in Kibonge forest. Afforestation, use of legislature and public awareness are possible mitigation measures.